STRUCTURAL FEATURES OF ECONOMICALLY-ALLOYED STEEL 20HGNMB AFTER CHEMICAL AND THERMAL HARDENING - S. P. Rudenko; A. A. Shipko; A. L. Valko; A. N. Chichin (Литьë и металлургия)
It is established that structural characteristics of the parts produced of industrial steel melting correspond to the requirements rendered to quality of the cemented layer and core of high-intense gear wheels according to the results of spectral, metallographic, X-ray structural and durometric analyses.